2021
DOI: 10.1111/ctr.14332
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of dengue in renal transplant recipients: A retrospective cohort from a single center

Abstract: Dengue virus belongs to the Flaviviridae genus. Flavivirus is a small, enveloped, and single-stranded RNA virus having a genome of positive polarity. 1 It is transmitted by Aedes aegypti and Aedes albopictus mosquitoes. DEN1, DEN2, DEN3, DEN4 are the four serovars of dengue. 2 WHO estimates that 500 000 people with severe dengue need hospitalization per year with 2.5% case fatality annually. 3 In 2019 India reported more than 67 000 cases of dengue fever according to data released by the Directorate of the Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…In our center, a previous study of invasive fungal infection reported 25% graft loss. 28 Similarly dengue cohort 29 from our center reported 6.4% acute rejection and 6.4% graft loss. Our preliminary report hence do not suggest any increased risk of graft loss or rejection compared to other infections…”
Section: Discussionmentioning
confidence: 91%
“…In our center, a previous study of invasive fungal infection reported 25% graft loss. 28 Similarly dengue cohort 29 from our center reported 6.4% acute rejection and 6.4% graft loss. Our preliminary report hence do not suggest any increased risk of graft loss or rejection compared to other infections…”
Section: Discussionmentioning
confidence: 91%